Influence of Blend Ratio and Processing Additive on Free Carrier Yield and Mobility in PTB7:PC(71)BM Photovoltaic Solar Cells - Pranculis, Vytenis (J Phys Chem C Nanomater Interfaces, 2016)
[Image: see text] Charge separation and extraction dynamics were investigated in high-performance bulk heterojunction solar cells made from the polymer PTB7 and the soluble fullerene PC(71)BM on a broad time scale from subpicosecond to microseconds using ultrafast optical probing of carrier drift and the integral-mode photocurrent measurements. We show that the short circuit current is determined by the separation of charge pairs into free carriers, which is strongly influenced by blend composition. This separation is found to be efficient in fullerene-rich blends where a high electron mobility of >0.1 cm(2) V(–1) s(–1) is observed in the first 10 ps after excitation. Morphology optimization using the solvent additive 1,8-diiodooctane (DIO) doubles the charge pair separation efficiency and the short-circuit current. Carrier extraction at low internal electric field is slightly faster from the cells prepared with DIO, which can reduce recombination losses and enhance a fill factor.